علامات (تزمين) الخطابات المحكية في القرآن: مقاربة تحليلية لنماذج مختارة من الآيات - الذنيبات، فايز مد الله سلمان; جرادات، مازن أحمد (الجامعة الأردنية - عمادة البحث العلمي, 2022)
تتناول هذه الدراسة عينة من الآيات القرآنية التي نقلها لنا القرآن على ألسنة قائليها (الخطاب المحكي)، وكانت فكرة الدراسة منطلقة من الكشف عن العلامات الزمنية لتلك المقولات من حيث كونها قيلت في سياق وموقف واحد، أم أنها قيلت في مراحل زمنية مختلفة وقد جمعها القرآن دفعة واحدة. وقد أثبتت الدراسة نوعين من علامات التزمين السياقية التي يمكن من خلال معرفة تتابع المقولات في سياق زمني واحد، أو تفرقها على أزمنة مختلفة، وهذه العلامات تستطيع أن تحسم جدلا دار حول تأويل بعض المواطن التي وردت فيها الخطابات المحكية. كما يمكن لهذه العلامات الكشف عن وجه جديد من وجوه إحكام الصياغة القرآنية. This study deals with a one sample of the Qur’anic verses that the Qur’an has (transmitted to us)\ been mentioned in the Qur’an (in the tongues of) according to those who say it (spoken discourse). The idea of the study was based on the disclosure of the (time marks)\ approximate dates of these statements in terms of being said in (one) single context and position, Or was it spoken in different stages of time. The Qur’an collected it all at once. The study has demonstrated two types of contextual signs of binding, which can be learned by knowing the sequence of statements in one time context, or separate them at different times, These signs can (settle) solve a controversy (surrounding) concerning the interpretation of some of the (citzens) ordinary people in which the spoken (letters) discourse was mentioned. These signs can also reveal a new aspect of (the tightening) making the Qur’anic wording more sound and solid.
Keywords: تفسير القرآن -- الآيات القرآنية -- البلاغة القرآنية -- الخواص الأسلوبية